Estudo dos aspectos clínico-epidemiológicos e microbiológicos e fatores de risco para infecção de corrente sanguínea em pacientes transplantados renais - Silva Júnior, Moacyr [UNIFESP] (2009)
Objectives: To evaluate, in kidney-transplant patients, the clinical-epidemiological and microbiological aspects, and the risk factors for the occurrence and mortality by BSI (blood stream infection). Methods: through the retrospective analyses of medical charts, we evaluated all episodes of blood stream infection that occurred in patients submitted to kidney transplants from January 1st, 2000 to January 31st, 2006 in the São Paulo Hospital and the Rim e Hipertensão Hospital. Through the study of the control-case (1:1, pairing the controls for age and time when the transplant took place) the risk factors for the occurrence of early and late BSI (before and after six months of the transplant) were analysed using multivaried analysis. For the analysis of risk factors related to death by BSI, the internal control group was used, comparing those who survived or died in a month after the event. Results: 185 patients were included for the risk factor analysis. The incidence was of 4.11% (considering only 136 patients transplanted between 2000 and 2006). The majority was from Rim Hospital (157 patients or 84.9%), 108 (58.4%) were female, average age of 44.26 years old and 53% received the graft from a living donor. The most frequent primary source of infection was the urinary tract. The Gram-negative bacteria prevailed, being the principal isolated agent Escherihia coli (30.3%). The early BSI was associated to acute posttransplant rejection (OR=3.69 e IC95: 1.36-9.97, p=0.03), use of double catheter J after the transplant (OR=3.36 e IC95: 1.50-7.52 p=0.002) and being the recipient of graft from a deceased donor (OR=3.16 e IC95: 1.39-7.17, p=0.001). In late BSI, the associated factors were patients with acute rejection (OR=4.04 e IC95: 1.78-9.17, p=0.001), Charlson index ≥ 3 (OR=6.98 e IC95: 2.43-20.01, p=0.01) and being the recipient of graft from a deceased donor (OR= 3.37 e IC95: 1.73-6.55, p=0.001 ). Related to mortality, the associated factors were APACHE II index ≥ 20 at the diagnoses of BSI (OR 6.39 IC95= 2.07-19.73,p=0.001), use of vasoactive drugs after BSI (OR 9.87 IC95= 2.95-32.94,p=0.001) and the need of mechanical ventilation (OR 7.66 IC95= 2.56-22.87, p=0.001). Conclusions: The urinary infection is the principal origin site of BSI, prevailing gram-negative bacteria as principal agents. Although factors related to the increase of the immune depression degree are risk factors during all the posttransplant period, the early BSIs are related to the use of double J catheter and the late ones to the presence of comorbidities. The mortality in 30 days is related to clinical gravity of the patient at the moment of and after the occurrence of the BSI.